Dukungan Strategis dan Operasional Pemerintah dalam Pemenuhan Hak Kesehatan Anak Tunagrahita di Kota Surabaya - Ana Riskhatul Fitria (Universitas Airlangga, 2018)
Background: Social justice is a condition of fulfilling material, spiritual and social needs of citizens to live properly and to develop themselves in carrying out the social functions. The social welfare rate in Indonesia was still low amounted to 62.8 in 2016. Children with mental illness problems experience social welfare. The government has provided support both strategic support and operational support for their lives.Aim: The objective of the research is to analyze the government's support for fulfilling child’s health rights for those who suffer from mental illness.Method: This research was descriptive. The data were collected by using policy review and observation. Policy review was used to discover the strategic support given by government to fulfill health needs of mentally illed children. Meanwhile, the observation was to find out government’s operational support for Kalijudan Surabaya Technical Implementation Unit (UPT) in Basic Social Services.Results: The results show that there is a good strategic support for the children with mental illness. The operational support has been implemented, but not in accordance with the existing regulations. However, Kalijudan Surabaya Technical Implementation Unit (UPT) in Basic Social Services has provided the right of health by cooperating with related parties.Conclusion: It can be concluded that the strategic support given includes Law Number 8 Year 2016 about disabled people, Health Ministry Law Number 25 Year 2014 about child’s health support, and Surabaya Mayor’s Law Number 2 Year 2013 about organization of Kalijudan Surabaya Technical Implementation Unit (UPT) at Basic Social Service Department. The Kalijudan Surabaya Technical Implementation Unit (UPT) in Basic Social Services had also given operational supports for mentally illed chidren’s health needs.Keywords: children with mental illness, health right, regulation